Participation by the poor in the fruits of growth - Mario La Fuente; Pedro Sádinz (CEPAL Review, 2001)
The influence of economic growth on numerous aspects of the economy and society is a frequently recurring topic among economists, especially at present, when profound economic and social transformations are under way in most of the countries of the region, while simultaneously there is an awareness that there are great shortcomings in terms of income distribution and that a high percentage of the population is in a state of poverty. A strong desire therefore exists to determine the capacity of economic growth to cope with those problems. This article begins by placing the issue in a conceptual and Latin American context and then going on to analyse it in the light of abundant statistical evidence. In particular, the assertion made in a recent study that “growth is good for the poor” is subjected to analysis and testing in the Latin American context.